Relationship Between Self-Control With Cybersex Behavioral Tendencies and it’s Implication for Guidance and Counseling Services - Fitri Andani; Alizamar Alizamar; Afdal Afdal (Jurnal Neo Konseling, 2020)
The internet which is often used as a supply of various information and entertainment turns out to have many impacts. Impacts that are often caused are generally negative, one of which is the tendency of individuals to access matters relating to pornography or sexuality commonly known as cybersex. Cybersex can be interpreted as sexual activities, sexual shows or conversations that lead to matters relating to sexuality. But the reality in the field there are still students who access porn sites so that, can disrupt daily activities. If this problem is not resolved early on, this will have a negative impact on the individual. Allegedly one of the factors that influence it is self-control. Self-control is the ability to guide one's own behavior, the ability to emphasize or block impulses or impulse behavior. This study aims to determine the relationship between self-control and the tendency of cybersex behavior of students at Adabiah Padang Senior High School and the implications for guidance and counseling services. This type of research is a correlational descriptive study with quantitative methods. The population of this study was all male and female students of class X and XI majoring in Natural Sciences and Social Sciences at Adabiah Padang Senior High School, with a total sample of 149 students. Sample selection using Purposive Sampling technique. The research instrument used was a self-control questionnaire and cybersex with a Likert scale model. The results revealed that (1) the tendency of cybersex behavior of students in Adabiah Padang senior high school on average was categorized very high, (2) Self-control of students in Adabiah Padang senior high school was on average categorized low (3) There was a significant negative relationship between self-control with the tendency of cybersex behavior of students at Adabiah Padang Senior High School. Based on the research findings, it is suggested to the school counselor to be able to provide counseling services namely information services, content mastery services, individual counseling services, group counseling services and group guidance in order to help students who have self-control problems and cybersex behavioral tendencies.